Manajerial Dakwah Islam Melalui Perayaan Sekaten Sebagai Representasi Kekayaan Kebudayaan Islam Indonesia - Muhammad Fatih Arroichan; Rasmuin Rasmuin (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2023)
This research aims to find out the strategies and managerial processes of da'wah contained in the sekaten tradition in responding to the richness of religion, culture, and the background of the Indonesian people. The researcher's approach in this study was to use a qualitative research methodology using library research methods. In this case, the author tries to collect material using various bibliographical data from various sources, including books, notes, and previous research articles. The Sekaten tradition is a celebration held in Yogyakarta, Indonesia, which has a close relationship with Islamic religious values. In this celebration, there are various elements related to Islamic da'wah. Overall, the Sekaten tradition has become an important vehicle for spreading Islamic da'wah and strengthening the community's religious identity. Through the transmission of Islamic teachings, moral and ethical development, as well as motivation and inspiration, the Sekaten celebration makes a positive contribution in the formation of individuals who are faithful, pious, and have concern for religious values ​​in everyday life.